Aerobic oxidative cyclization of benzamides via meta-selective C–H tert-alkylation: rapid entry to 7-alkylated isoquinolinediones. Issue 24 (15th February 2016) - Tang, Shi; Deng, You-Lin; Li, Jie; Wang, Wen-Xin; Wang, Ying-Chun; Li, Zeng-Zeng; Yuan, Li; Chen, Shi-Lu; Sheng, Rui-Long
Abstract : A novel copper-catalyzed aerobic oxidative cyclization of benzamides via meta -selective tert -alkylation using AIBN and analogues as radical precursors was described. Abstract : A novel copper-catalyzed aerobic oxidative cyclization of benzamides via meta -selective C–H tert -alkylation using AIBN and analogues as radical precursors was described. This strategy provides an elusive and rapid means to 7- tert -alkylated isoquinolinediones, as well as the construction of tertiary alkyl–aryl C(sp 3 )–C(sp 2 ) bonds with positional selectivity.